Forms and Stages of Community Participation in Kelompok Usaha Bersama (KUBE) Alkesa Lestari Cipedak Jagakarsa South Jakarta - Muhtadi, Muhtadi; Hanum, Lifya Afrianti (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2024)
This research on Community Participation in the KUBE Program at the Alkesa Lestari Joint Business Group (KUBE) Cipedak, Jagakarsa, South Jakarta discusses how community participation in the KUBE program which is one of the work programs of the Ministry of Social Affairs, also discusses the forms and steps of community participation in running business programs at KUBE Alkesa Lestari. This research uses a qualitative approach with descriptive methods described by written words and numbers. The data collection techniques used are observation, interviews, and documentation. The theory used explains the form and ladder of community participation. The results of the research show that from the planning stage members have not been involved. The implementation stage of the community has contributed well in running the KUBE program. The institutionalization stage of member participation has been well involved. The monitoring and evaluation stage of KUBE Alkesa Lestari members are still not involved but can be involved by providing assessments and suggestions for the KUBE program.